Design of experiments for validation of multiaxial high cycle fatigue criteria - Olofsson, Niklas (My University, 2017)
GKN Aerospace is a world leading supplier of aerospace engine components, continuously improving their design methods. One important area is the evaluation of high cycle fatigue (HCF) at multiaxial stress states. A critical plane criterion has been suggested to replace the currently used invariant criterion in order to improve accuracy. However, experiments are required to support and verify the choice of criterion. Through a numerical comparison of criteria, states of stress where predictions differ are identified. Among them, biaxial stress states with high mid stresses are of special interest since such are often present in rotating engine components. Therefore, a testing method able to generate this state of stress is desirable. A literature review shows that the two most commonly used biaxial testing methods are cruciform specimens loaded in two directions, and tubular specimens with internal pressure. However, both methods require complex, expensive and rare laboratory equipment. Hence, alternative methods are sought. Several concepts are developed and their feasibility are evaluated through numerical simulations. Recommendations regarding specimen geometry, test setup and failure detection are given. Finally, advantages and concerns for the concepts are summarised. The Disc bending-concept is considered to be most promising. It constitutes a disc-shaped specimen, simply supported at its edges and transversely loaded in the centre region. This set up creates a biaxial bending stress state, with a close to uniform stress distribution. The concept may be thought of as a biaxial version of the uniaxial four point bending technique.
Keywords: Materialvetenskap; Produktion; Transport; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Teknisk mekanik; Rymd- och flygteknik; Materials Science; Production; Transport; Sustainable Development; Innovation & Entrepreneurship; Applied Mechanics; Aerospace Engineering